Effects of Mg²⁺ pretreatment and the modulation of Mg²⁺-sensitive cardiac ion channels on Ca²⁺ paradox phenomenon in the heart - Alatrag, Fatma (Department of Human Biology, 2016)
The aim of this study was to investigate the effects of Mg²⁺ pretreatment and of pharmacological inhibitors of TRPM7 channels on CP-induced cardiac injury in the isolated rat heart.